Using an Online Platform for Conducting Face-To-Face Interviews - Wakelin, Karen; Fleming, Tania; McAra-Couper, Judith (SAGE Publishing, 2024)
Semi-structured interviews are useful for exploring participants experiences, understandings, and opinions on a particular issue. Traditionally, interviews have taken place in-person however, because of in-person restrictions with Covid-19, and with the changing landscape of online connection, opportunities have arisen for how to conduct interviews using an online platform. The purpose of this article is to highlight the first author’s experiences with using an online platform to conduct face-to-face interviews and the valuable contribution that online interviewing could offer as a valid research tool that differs to that of in-person face-to-face interviews. Online semi-structured interviews were conducted with fourteen midwives and five pregnant people from New Zealand using Microsoft Teams. Interviews were videorecorded and conducted as part of a larger mixed methods multiphase study to explore participants experiences with how they use communication technology to connect with one another. The interviews took place between September 2022 – May 2023. Two key areas which highlight the benefits and challenges with online interviews were identified. These were around the potential to ‘capture the essence of the person’ and through the flexibility of the technology in enabling FTF connections. Challenges were also noted around connectivity issues. Videorecording online interviews offered an ability to capture the ‘essence of the person’ through visual and auditory cues. These same cues were shown to assist with lipreading when transcribing inaudible words which can assist in the analysis of data. There were disruptions to some interviews due to interviewing taking place in the person’s home and connectivity issues, however, these were felt to be minimal. Online interviewing should not be considered a ‘poor relation’ to in-person face-to-face interviews, but instead, a valuable option that contributes towards the growing body of knowledge around online interviewing as a valid research tool that is different from face-to-face.
Keywords: 1110 Nursing; 1607 Social Work